2020
DOI: 10.1101/2020.06.29.179234
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Centromere evolution in the fungal genusVerticillium

Abstract: ABSTRACTCentromeres are chromosomal regions that are crucial for chromosome segregation during mitosis and meiosis, and failed centromere formation can contribute to chromosomal anomalies. Despite this conserved function, centromeres differ significantly between and even within species. Thus far, systematic studies into the organization and evolution of fungal centromeres remain scarce. In this study, we identified the centromeres in each of the ten species of the fungal genus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 116 publications
(114 reference statements)
0
4
0
Order By: Relevance
“…We recently reported that wild-type V. dahliae displays relatively low levels of DNA methylation, with an average of ∼0.4% methylation in CG and CHG context and essentially no DNA methylation in CHH context (Cook et al ., 2020). DNA methylation in V. dahliae is restricted to particular inactive transposons that locate in condensed, H3K9me3-enriched, chromatin regions in the core genome, including those localized in centromeres (Figure 3A) (Cook et al ., 2020; Seidl et al ., 2020). We furthermore showed that the Δ Hp1 mutant lost all DNA methylation, indicating that Hp1 is required for cytosine methylation and V. dahliae DNMTs cannot methylate DNA independently (Cook et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported that wild-type V. dahliae displays relatively low levels of DNA methylation, with an average of ∼0.4% methylation in CG and CHG context and essentially no DNA methylation in CHH context (Cook et al ., 2020). DNA methylation in V. dahliae is restricted to particular inactive transposons that locate in condensed, H3K9me3-enriched, chromatin regions in the core genome, including those localized in centromeres (Figure 3A) (Cook et al ., 2020; Seidl et al ., 2020). We furthermore showed that the Δ Hp1 mutant lost all DNA methylation, indicating that Hp1 is required for cytosine methylation and V. dahliae DNMTs cannot methylate DNA independently (Cook et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Sexual reproduction has not been reported for V. dahliae that is presumed to mainly reproduce asexually (de Jonge et al ., 2013). Recently, we demonstrated that DNA methylation in V. dahliae requires Hp1 and is restricted to H3K9me3-enriched transposons that localize mainly in evolutionary stable core genomic regions that are typically shared across different V. dahliae strains, including centromere regions (Cook et al ., 2020; Seidl et al ., 2020). In contrast to stable core regions, genomic regions that are important for adaptation show extensive presence-absence polymorphisms between V. dahliae strains, and are therefore designated as lineage-specific (LS) (Klosterman et al ., 2011; de Jonge et al ., 2013; Faino et al ., 2016; Depotter et al ., 2019; Cook et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Sexual reproduction has not been reported for V. dahliae that is presumed to mainly reproduce asexually (de Jonge et al, 2013). Recently, we demonstrated that DNA methylation in V. dahliae requires Hp1 and is restricted to H3K9me3-enriched transposons that localize mainly in evolutionary stable core genomic regions that are typically shared across different V. dahliae strains, including centromere regions (Cook et al, 2020;Seidl et al, 2020). In contrast to stable core regions, genomic regions that are important for adaptation show extensive presenceabsence polymorphisms between V. dahliae strains, and are therefore designated as lineagespecific (LS) (Klosterman et al, 2011;de Jonge et al, 2013;Faino et al, 2016;Depotter et al, 2019;Cook et al, 2020).…”
Section: Introductionmentioning
confidence: 88%
“…We recently reported that wild-type V. dahliae displays relatively low levels of DNA methylation, with an average of ~0.4% methylation in CG and CHG context and essentially no DNA methylation in CHH context (Cook et al, 2020). DNA methylation in V. dahliae is restricted to particular inactive transposons that locate in condensed, H3K9me3-enriched, chromatin regions in the core genome, including those localized in centromeres ( Figure 3A) (Cook et al, 2020;Seidl et al, 2020). We furthermore showed that the ∆Hp1 mutant lost all DNA methylation, indicating that Hp1 is required for cytosine methylation and V. dahliae DNMTs cannot methylate DNA independently (Cook et al, 2020).…”
Section: Dim2 Is the Main Dna Methyltransferase In V Dahliaementioning
confidence: 98%